Economic and Financial Crimes in Nigeria and the Curbing Effect of Some Precautionary Measures of Islamic Law - Olagunju - Ibrahim, Ridwan Olawale (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
Economic and financial crime constitutes one major area of headache for almost all countries of the world today. The totality of havoc the crime unleashes day in day out on the affected states is more than what can be described in a jiffy. Evolvement of legal and institutional frameworks is what the successive governments of various nations are resulting to as an attempt to bring forth a game changer device to the menace of this crime. Despite these efforts at the instance of the affected states, the problem is still unabated thereby constituting one serious area of worry continuously at the global level with untold economic and financial hardship being the implication thereof. Nigeria is no doubt in the entanglement of this problem. Knowing fully well that the Islamic Law compliant states like Iran fare relatively better in terms of this heat of economic and financial crime, effort is dissipated in this paper to look through some impressive measures of Islamic Law whose implementation against the crime in the early pristine period of Islam, and to an extent in some contemporary Islamic law states, has had some curbing effects on the particular crimes.